2015
DOI: 10.1371/journal.pone.0135820
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heritage of the Balto-Slavic Speaking Populations: A Synthesis of Autosomal, Mitochondrial and Y-Chromosomal Data

Abstract: The Slavic branch of the Balto-Slavic sub-family of Indo-European languages underwent rapid divergence as a result of the spatial expansion of its speakers from Central-East Europe, in early medieval times. This expansion–mainly to East Europe and the northern Balkans–resulted in the incorporation of genetic components from numerous autochthonous populations into the Slavic gene pools. Here, we characterize genetic variation in all extant ethnic groups speaking Balto-Slavic languages by analyzing mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 53 publications
7
61
0
7
Order By: Relevance
“…Bulgarians, Croats, Serbs, Slovenes) (cited in [10, 11]). A recent study of autosomal, mitochondrial and Y-chromosomal data coined the existence of two sub-groups that presumably existed some 1900 years ago, namely the East-West Slavs (from Poland to the Volga river) and the South Slavs (confined to the Balkan Peninsula) [12]. Moreover, the study revealed pronounced genetic similarities between the Czechs and their immediate Germanic neighbors while, further north, the Sorbs and the surrounding Germans were clearly genetically distinct [13].…”
Section: Introductionmentioning
confidence: 99%
“…Bulgarians, Croats, Serbs, Slovenes) (cited in [10, 11]). A recent study of autosomal, mitochondrial and Y-chromosomal data coined the existence of two sub-groups that presumably existed some 1900 years ago, namely the East-West Slavs (from Poland to the Volga river) and the South Slavs (confined to the Balkan Peninsula) [12]. Moreover, the study revealed pronounced genetic similarities between the Czechs and their immediate Germanic neighbors while, further north, the Sorbs and the surrounding Germans were clearly genetically distinct [13].…”
Section: Introductionmentioning
confidence: 99%
“…The data for Belarussians are 9.6% (Kushniarevich et al, 2013;Kushniarevich et al, 2015) and for Ukrainians-5.7% (Battaglia et al, 2009;Kushniarevich et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the Slavic mtDNA landscape, Slavic speaking populations is different (Kushniarevich et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations